2009
DOI: 10.1159/000261836
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analyses of Fifty Supracricoid Laryngectomized Specimens: Evidence Base Supporting Minimal Margins

Abstract: Objectives: Supracricoid laryngectomy (SCL) is a reliable laryngeal preservation surgery. However, close surgical margins are often inevitable. Based on clinicopathological analyses of supracricoid laryngectomized specimens, we evaluated the evidence base supporting minimal margins. Methods: The distance between tumor edge and resected margin was measured macro- and microscopically at the anterior, posterior, superior and inferior edges, using 50 surgical specimens. The margins were correlated with pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Among the three goals, continuous oncological control is by far the most important for the success of SCL-CHEP. Better oncological control essentially relies on better local and regional control (14)(15)(16). Local recurrence of SCL-CHEP has been reported at rates of 5-8% (3,4,8-11), compared with 18-31% in conventional partial laryngectomies (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three goals, continuous oncological control is by far the most important for the success of SCL-CHEP. Better oncological control essentially relies on better local and regional control (14)(15)(16). Local recurrence of SCL-CHEP has been reported at rates of 5-8% (3,4,8-11), compared with 18-31% in conventional partial laryngectomies (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The surgical potential of SCL-CHEP has been confirmed to be able to cope with tumor excisions with margins of a few millimeters at the anterior, posterior and superior glottis except for the inferior glottis (14). An intraoperative margin study was reported to be useful for ensuring the validity of SCL-CHEP (15).…”
Section: Introductionmentioning
confidence: 93%
“…When treating early glottis cancer with TLM, a 1–2 mm free margin from the tumor line is sufficient to guarantee a complete resection 11,15,16. In order to obtain good functional results the resection is tailored to the clinical appearance of the tumor, sparing as much tissue as possible of the vocal cord.…”
Section: Assessment Of Margins In Endoscopic Surgery—glottic Cancermentioning
confidence: 99%
“…After introducing SCPL to our institute in 1997, the number of surgical cases increased as we gained experience; after 2003, the number of SCPL performed annually surpassed the number of total laryngectomies [9,10]. Postoperative complications, especially wound infection, were frequently encountered in our early stage patients.…”
Section: Discussionmentioning
confidence: 96%